MATHEMATICAL MODEL of STIRRING REFLECTIONS FOR the MONOPULSE peak DIRECTION FINDER - S. A. Gorshkov; E. N. Builov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The mathematical model of formation of stirring reflexions from a spreading surface and hydrometeors with reference to the peak monopulse direction finder, considering spatial correlation of hindrances in reception channels is considered.